ANALISIS STRATEGI PEMASARAN PADA PRODUK SIMPANAN MUDHARABAH DI BMT NUSANTARA CABANG GLENMORE - Yeny Rokhilawati (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2022)
A marketing strategy is a plan to allocate and coordinate resources in marketing activities to achieve both short- and long-term goals based on market research on product valuation, promotion and sales planning and retribution. To achieve maximum marketing results, it is first necessary to apply the core concept of marketing that determines segmentation or grouping, targeting (target market) and positioning (company position). This research uses qualitative research methods with qualitative descriptive approaches, data collection, using several methods namely obsevation, interviews and documentation. While technical data analysis uses qualitative data analysis (data reduction, data presentation and conclusion withdrawal). While checking the validity of data using source triangulation and triangulation techniques. The results of this research, it can be concluded that the marketing strategy carried out by BMT UGT Nusantara is marketing mix 11 in the form of products (products) is fairly complete, the price (price) is very cheap, the place (place) by picking up the ball, promotion (promotion) more to field officers and brochures, people (people) are male employees and prioritize graduates of boarding schools, concern (public relations) by giving fines obtained from customers to be donated to social institutions, Physical evidence (physical evidence) by setting up an office and there is written evidence of transactions, power (power) with a strong network and customers quite a lot. (Pressure) in working employees must run on time and full responsibility, performance (performance) is to determine who employees who have good performance will be raised and vice versa, and a good process , friendly and polite will give its own impression for customers.